1983
DOI: 10.1300/j019v04n02_03
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Graduated Exposure, Verbal Coping Skills, and Their Combination in the Treatment of Children's Fear of the Dark

Abstract: This study investigated the effectiveness of graduated exposure, verbal mping skills, and their combination in treating fear of the dark in 4and 5-year-old normal children, using both be-, havioral and subjective measures of fearfulness. Only those groups which received direct exposure to the dark during treatment demonstrated significant changes in dark tolerance. Non-significant differences in dark tolerance for high versus low instructiond demand conditions in two posttests were obtained. Analysis of subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
4

Year Published

1985
1985
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 0 publications
0
26
0
4
Order By: Relevance
“…Theoretically, treatment principles are based on the use of operant procedures, shaping and extinction, used during repeated and controlled graduated exposures, with therapists providing reinforcement and verbal feed-back for overcoming avoidance behavior (Davis & Ollendick, 2005). Three randomized controlled studies have compared the efficacy of graduated exposure with verbal coping skills (Sheslow, Bondy, & Nelson, 1983), vicarious exposure (Menzies & Clarke, 1993) or computer-aided vicarious exposure (Dewis et al, 2001) in children with phobias or assessed as having severe fears.…”
Section: Graduated In-vivo Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, treatment principles are based on the use of operant procedures, shaping and extinction, used during repeated and controlled graduated exposures, with therapists providing reinforcement and verbal feed-back for overcoming avoidance behavior (Davis & Ollendick, 2005). Three randomized controlled studies have compared the efficacy of graduated exposure with verbal coping skills (Sheslow, Bondy, & Nelson, 1983), vicarious exposure (Menzies & Clarke, 1993) or computer-aided vicarious exposure (Dewis et al, 2001) in children with phobias or assessed as having severe fears.…”
Section: Graduated In-vivo Exposurementioning
confidence: 99%
“…In the study by Sheslow, Bondy, and Nelson (1983), 32 children in private day-care, aged 4 to 5 years, were recruited via a parental survey report on children's fear of the dark. The children who met a criterion of strong fear of the dark from two repeated behavioral avoidance tests (32 of 74 (43%)), were matched for gender and duration of dark tolerance and randomized to one of four conditions: 1.…”
Section: Graduated In-vivo Exposurementioning
confidence: 99%
“…Existem evidências de que sejam mais eficazes do que modelagem ao vivo e estratégias verbais de autocontrole (Sheslow et al, 1983;Menzies e Clarke, 1993;Silverman et al, 1999).…”
Section: Transtornos De Ansiedade E Fobiasunclassified
“…Sheslow et al [93] provided yet another demonstration of the effectiveness of reinforced practice. This study compared reinforced practice (labelled graduated exposure by the authors), verbal coping skills and their combination in treating fear of the dark in 32 young children (4 to 5 years old).…”
Section: Contingency Managementmentioning
confidence: 99%
“…Thus, on the basis of these four randomized control studies, it can be concluded that reinforced practice has also earned well-established status: it has been shown to be more effective than no-treatment control conditions in two studies [91,92] and to be superior to two other treatment modalities, verbal coping skills [93] and live (adult) modelling [28,36], both of which have been shown to be more effective than no treatment.…”
Section: Contingency Managementmentioning
confidence: 99%